Coaker film rushes : Interview with Mr. Josiah Kearley and others. Part 2 - Memorial University of Newfoundland. Extension Service (Producer) (Memorial University of Newfoundland. Extension Service, 1970)
Mr. Josiah (Joe) Kearley and others speak about William Coaker and their personal memories of the man.